Deficient skin proteins rescue of expression in patients with epidermolysis bullosa: efficacy of gentamicin - Olga G. Artamonova; Arfenya E. Karamova; Alexey A. Kubanov; Vadim V. Chikin; Ekaterina S. Monchakovskaya (State Scientific Center of Dermatovenereology and Cosmetology, 2024)
Epidermolysis bullosa is a group of rare hereditary skin diseases based on mutations in the genes of structural proteins of the epidermis and the dermal-epidermal junction. Clinically, epidermolysis bullosa is characterized by the appearance of erosions and blisters on the skin and mucous membranes in response to any minor impact. Currently, the treatment of epidermolysis bullosa is only symptomatic. Pathogenetic methods of the epidermolysis bullosa therapy are under development. One of the new possible pathogenetic directions in the treatment of epidermolysis bullosa is aminoglycoside antibiotics (gentamicin, geneticin, paromomycin). A number of studies have shown the ability of gentamicin to promote readthrough terminating codon and resume the synthesis of type VII collagen in keratinocytes and fibroblasts in patients with epidermolysis bullosa with nonsense mutations in the COL7A1. The review presented the possibilities of gentamicin therapy for patients with epidermolysis bullosa, describes the mechanism of its action, summarizes data from clinical trials.